Child Psychology / The Modern Science - Haith Marshall M; Miller Scott A; Vasta Ross (John Wiley & Sons, Ltd, 1995)
Foundations of a Science, Introduction and Perspective, Theories of Child Development, Research Methods, Biological and Physical Development, Genetics: The Biological Context of Behavior, Prenatal Development, Birth and Physical Growth and the Development of Skill, Cognitive Development, Sensory and Perceptual Development, Cognitive Development: The Piagetian Approach, Cognitive Development: The Information-Processing Approach, Cognitive Development: The Intelligence Test Approach, Language Development, Social and Personality Development, Early Social and Emotional Development, Development of the Self, Moral Development, Gender-Role Development and Sex Differences, Peer Relations.